2016
DOI: 10.1039/c5ee03503a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proton and electron reservoir abilities of polyoxometalate grafted on graphene for high-performance hydrogen evolution

Abstract: A 3D configuration of high-quality graphene sheets and a polyoxometalate [H7P8W48O184]33− showing excellent hydrogen evolution activity at extremely low overpotential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 66 publications
3
109
0
Order By: Relevance
“…[84][85][86] Several reports can be found in the literature concerningt he immobili-zation of POMs in carbon materials, which include multi-walled carbon nanotubes (MWCNT), [87][88][89] single-walledc arbon nanotubes (SWCNT), [90][91][92][93] mesoporous carbons, [94] activated carbons (AC), [95] graphene, [90,91,96] and graphene oxide. [81,97] Awaga et al [92,93] developed POM@carbonh ybridst hat were used as cathode materials in rechargeablel ithium batteries. The POMs were attached to the SWCNT through the electrostatic attraction betweent he nBu 4 N + counter ions that interacted with the SWCNT,c reating positive sites, and the negatively charged PMo 12 .S imilar work was developedb yF ernandes et al [90,91] where severalK eggin-type POMs (PMo 12 ,P Mo 11 ,P Mo 11 V, or PMo 10 V 2 )w erei mmobilized onto SWCNT,g raphene flakes (GF) or carbon black Vulcan (CBV).…”
Section: Polyoxometalate-based (Nano)compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…[84][85][86] Several reports can be found in the literature concerningt he immobili-zation of POMs in carbon materials, which include multi-walled carbon nanotubes (MWCNT), [87][88][89] single-walledc arbon nanotubes (SWCNT), [90][91][92][93] mesoporous carbons, [94] activated carbons (AC), [95] graphene, [90,91,96] and graphene oxide. [81,97] Awaga et al [92,93] developed POM@carbonh ybridst hat were used as cathode materials in rechargeablel ithium batteries. The POMs were attached to the SWCNT through the electrostatic attraction betweent he nBu 4 N + counter ions that interacted with the SWCNT,c reating positive sites, and the negatively charged PMo 12 .S imilar work was developedb yF ernandes et al [90,91] where severalK eggin-type POMs (PMo 12 ,P Mo 11 ,P Mo 11 V, or PMo 10 V 2 )w erei mmobilized onto SWCNT,g raphene flakes (GF) or carbon black Vulcan (CBV).…”
Section: Polyoxometalate-based (Nano)compositesmentioning
confidence: 99%
“…The POMs were attached to the SWCNT through the electrostatic attraction betweent he nBu 4 N + counter ions that interacted with the SWCNT,c reating positive sites, and the negatively charged PMo 12 .S imilar work was developedb yF ernandes et al [90,91] where severalK eggin-type POMs (PMo 12 ,P Mo 11 ,P Mo 11 V, or PMo 10 V 2 )w erei mmobilized onto SWCNT,g raphene flakes (GF) or carbon black Vulcan (CBV). Liu et al [97] reported ao ne-step electrochemical reduction synthesis of P 8 [98] or with SWCNT. [88] Kulesza's group [99][100][101][102] has also been actively workingi nt he fieldo fc arbon nanotubes modified with Keggin and Dawson-type POMs, namely [PMo 12 O 40 ] 3À and [P 2 W 17 VO 62 ] 8À for different applications: electrocatalysis, charge storaged evices, and fuel cells.…”
Section: Polyoxometalate-based (Nano)compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18] Currently,t hese materials are still hampered by their low electricalc onductivity and their fast degradation due to irreversible redox processes on the surfaceo ft he material. Although molecular polyoxometalates (POMs) are well known for their multielectront ransfer reactivity (e.g.,f or the OER, ORR, and hydrogen-evolution reactions), [27][28][29][30] their stable linkaget oc onductive substrates is still ac hallenge owing to their solubility in many commone lectrolytes, particularly in water. [19][20][21][22][23] Although top-downs yntheses of transition-metal oxide/carbide-carbon composites have been explored in detail,t he bottom-up fabrication of such composites starting from molecular metal oxide precursors has only recently become af ocus in the design of energy materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al. presented the P 8 W 48 /rGO nanomaterial as an efficient electrocatalyst for the HER in acidic aqueous solution . Ma et al.…”
Section: Introductionmentioning
confidence: 99%